Gender Stereotypes in Digital Technologies for Teaching and Learning in TVET Programs of Northern Mindanao, Philippines - Gutierrez, Michelle Samantha; Silor, Adelfa; Leuterio, Jan Vincent; Ramayan, Avril Joy; Silor, Faith Stephanny (Journal of Technical Education and Training, 2025)
This study examines gender stereotypes in the use of digital technologies for teaching and learning in Technical and Vocational Education and Training (TVET) programs in Northern Mindanao, Philippines. Using a descriptive research design, the study identifies the extent of gender stereotyping in digital technologies, while an independent sample t-test was employed to determine significant differences in perceptions between male and female respondents. The study involved faculty members from selected public and private Higher Education Institutions (HEIs) in Region 10 offering technology education programs. Findings indicate that while faculty members generally exhibit positive attitudes toward gender inclusivity, disparities persist in their perceptions of gender-stereotyped classroom practices. Participants disagreed with the notion that the government is not doing enough to raise awareness of gender issues, suggesting either a lack of clarity in government initiatives or limited public awareness of existing measures. Nevertheless, respondents strongly agreed that teachers should promote respect for all genders in educational settings. Although certain levels of gender insensitivity were observed, the overall findings suggest that gender stereotyping in the use of digital technologies within TVET programs is not highly pervasive. This study underscores the importance of continuous efforts to foster gender-inclusive practices in digital learning environments.